The Model of Supervision over Administrative Courts in Poland - Jan Olszanowski (Bratislava Law Review, 2020)
One of the most significant current discussions in Polish legal doctrine is how actions of executive powers, especially supervisory measures can affect judicial independence. It is related to basic constitutional and administrative law issues, including the separation of powers, the independence and the impartiality of the judiciary, the independence of the courts, the supervision and control, the efficiency and effectiveness of judicial protection. The analysis focuses on the dependence between the model of administrative supervision adopted in administrative justice and the efficiency of the courts, as well as their perception by the public. The study will examine supervisory measures aimed at ensuring the efficient functioning of the courts. The effectiveness of judicial review of administrative justice is essential for the protection of individuals' rights and the functioning of the state authorities in both the social and the economic sphere. From an extrajudicial point of view its significance is reflected in the influence on the judiciary, which will not only be effective in its procedural activity, but also in the level of trust and social prestige. It holds that the three arms of the state – the executive, the judiciary and the legislature – should, to a greater or lesser extent, be kept separate. That way, they are able to hold one another to account. This theory about the separation of state power went on to have a formative effect on the development of modern-day democracies. And it’s this vision of the tripartite separation of state power that is essential to the EU’s argument against the Polish reforms of the judiciary. The problem of supervision over administrative courts is also connected with external and internal independence of the judiciary. External independence refers to freedom from undue outside pressure, while internal independence protects individual judges from undue pressure from within the system. “Undue internal pressure” sometimes comes from court presidents and may take different forms: even where individual judges are not formally subordinate to court presidents or other authorities and may be result of attribution of workload, allocation of resources and benefits, disciplinary powers, powers of transfer and secondment, distribution of cases, etc. The aim of this paper is to examine the problem of supervision over administrative courts in legal system of Poland. The article focuses on the dependence between the model of administrative supervision and the efficiency of the courts.